Simultaneous Detection and Viral DNA Load Quantification of Different Human Papillomavirus Types in Clinical Specimens by the High Analytical Droplet Digital PCR Method - Rotondo, John Charles; Oton-Gonzalez, Lucia; Mazziotta, Chiara; Lanzillotti, Carmen; Iaquinta, Maria Rosa; Tognon, Mauro; Martini, Fernanda (Frontiers in Microbiology, 2020)
Human papillomaviruses (HPVs) are small DNA tumor viruses that mainly infect mucosal epithelia of anogenital and upper respiratory tracts. There has been progressive demand for more analytical assays for HPV DNA quantification. A novel droplet digital PCR (ddPCR) method was developed to simultaneously detect and quantify HPV DNA from different HPV types. DdPCR was initially tested for assay sensitivity, accuracy, specificity as well as intra- and inter-run assay variation employing four recombinant plasmids containing HPV16, HPV18, HPV11 and HPV45 DNAs. The assay was extended to investigate/quantify HPV DNA in Cervical Intraepithelial Neoplasia (CIN, n=45) specimens and human cell lines (n=4). DdPCR and qPCR data from clinical samples were compared. The assay showed high accuracy, sensitivity and specificity, with low intra-/inter- run variations, in detecting/quantifying HPV16/18/11/45 DNAs. HPV DNA was detected in 51.1% (23/45) CIN DNA samples by ddPCR, whereas 40% (18/45) CIN tested HPV-positive by qPCR. Five CIN, tested positive by ddPCR, were found to be negative by qPCR. In CIN specimens, the mean HPV DNA loads determined by ddPCR were 3.81 copy/cell (range 0.002-51.02 copy/cell), whereas 8.04 copy/cell (range 0.003-78.73 copy/cell) by qPCR. DdPCR and qPCR concordantly detected HPV DNA in SiHa, CaSki and Hela cells, whereas HaCaT tested HPV-negative. The correlation between HPV DNA loads simultaneously detected by ddPCR/qPCR in CINs/cell lines was good (R2=0.9706, p<0.0001). Our data indicate that ddPCR is a valuable technique in quantifying HPV DNA load in clinical samples, including CIN specimens and human cell lines.